2019
DOI: 10.15252/embr.201847283
|View full text |Cite
|
Sign up to set email alerts
|

The nucleoporin ELYS regulates nuclear size by controlling NPC number and nuclear import capacity

Abstract: How intracellular organelles acquire their characteristic sizes is a fundamental question in cell biology. Given stereotypical changes in nuclear size in cancer, it is important to understand the mechanisms that control nuclear size in human cells. Using a high‐throughput imaging RNAi screen, we identify and mechanistically characterize ELYS, a nucleoporin required for post‐mitotic nuclear pore complex (NPC) assembly, as a determinant of nuclear size in mammalian cells. ELYS knockdown results in small nuclei, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 126 publications
(175 reference statements)
6
37
0
Order By: Relevance
“…Note the intranuclear lamin B1 puncta in all three fibroblast lines as previously described in other cell lines [42][43][44] . Despite these similar variations in nuclear morphology in FADS and HGPS fibroblasts, expression of lamin A/C and lamin B1 in FADS fibroblasts was only slightly altered, whereas all three lamin isoforms were significantly reduced in HGPS cells compared to MRC5 cells ( Fig.…”
Section: Resultssupporting
confidence: 64%
“…Note the intranuclear lamin B1 puncta in all three fibroblast lines as previously described in other cell lines [42][43][44] . Despite these similar variations in nuclear morphology in FADS and HGPS fibroblasts, expression of lamin A/C and lamin B1 in FADS fibroblasts was only slightly altered, whereas all three lamin isoforms were significantly reduced in HGPS cells compared to MRC5 cells ( Fig.…”
Section: Resultssupporting
confidence: 64%
“…Nuclear area and intensity measurements were normalized to controls. Averaging and statistical analyses were performed for independently repeated experiments [ 29 ]. Two‐tailed Student's t -test assuming equal variances was performed using GraphPad PRISM 7 software to evaluate statistical significance.…”
Section: Methodsmentioning
confidence: 99%
“…In the budding and fission yeasts, it has been proposed that nuclear volume ( V nuc ) scales with cellular volume ( V cell ) (Jorgensen et al, 2007; Neumann and Nurse, 2007) and in the case of fission yeast, a nuclear to cellular volume (N/C) ratio of 8% is maintained over a 35-fold range of cell volumes. Although recent studies have identified some molecular players and biological processes with roles in nuclear size control (Brownlee and Heald, 2019; Cantwell and Nurse, 2019; Jevtić et al, 2019; Kume et al, 2019, 2017), it is not known how these are integrated in a global mechanism to maintain nuclear scaling in individual cells as they grow and divide. Investigation of this mechanism requires understanding of the kinetics of this process, in particular of how individual cells with aberrant N/C ratios correct towards the population mean and what this implies for the nuclear size control mechanisms employed by cells.…”
Section: Introductionmentioning
confidence: 99%